Risk preference and adoption of risk management strategies: Evidence from high-value crop production in emerging economy - Khanal, Aditya R.; Mishra, Ashok K.; Kumar, Anjani (Agricultural and Applied Economics Association, 2019)
Risk and risk preferences are considered as important drivers on farm management, crop choice, and land use decisions. A farmer’s choice of risk management strategies is of vital importance for the viability and continuation of the farm business. Using a primary survey data of onion growers in India and risk preference measures using risk elicitation techniques, we tested for the relationship between risk preference and different risk management decisions. We found a negative relationship between risk preference and adoption of farm diversification strategies, a positive relationship between risk preference and farm concentration and specialization, and a negative relationship between risk preference and adoption of good agricultural practices. Additionally, we found that high risk averse farmers are more likely to -adopt farm diversification strategies, -adopt higher number of good agricultural practices, -adopt improved government recommended seed varieties and –adopt preventive measures against diseases & pests, as compared to low risk averse farmers.